Gender dalam Perspektif Islam: Telaah Kritis Peran Wanita Muslimah di Indonesia - Sigit Tri Utomo (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2016)
In the era of modernization, as now women are considered equal to men .the women have the same rights in certain areas such as the right to obtain positions in the bureaucracy, the right to issue opinions and others.the opinion that developed in the community on the status of women and the world is still divided into pole opposite. On one hand, it is generally argued that women should have at home, devoted to her husband, and has a domestic role. On the other hand, the development of similarly suggested that women should be in accordance with their rights of freedom. The phenomenon of cases stemming from gender discrimination is still easily found in public life. Domestic violence, sexual exploitation of women and children in various forms such as trafficking, ostensibly as a labor, delivery art, marriage and various other gender problem still a social problem that needs their handling more serious and focused mainly on the government's attention.